The Meaning of the Philosophy of Bhuppha’, Bhabhu’, Ghuru, Ratoh in the Context of Decision Making Regarding Child Marriage in Bangkalan - Fitriyah Amin Daman; Ali Imron (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2022)
Child marriage is still prevalent in Indonesia. According to the NTCR data of Galis District 2019, Kelbung Village, Galis District, Bangkalan Regency still holds the highest percentage for child marriage in Galis District of 65.8 %, The Madurese people still firmly hold their philosophyregarding decision makers and figures to be respected in everyday life, namely bhuppha’, bhabhu’, ghuru, ratoh, which depict the hierarchy of figures whom shall be respected and whose decision shall be obeyed. Based on the philosophy, Madurese girls have the obligation to not to oppose any decisions that have been made by their parents, especially their fathers. This study aims to describe the meaning of the philosophy of bhuppha’, bhabhu’, ghuru, ratoh in the process of decision-making regarding child marriage in Kelbung Village, Galis District, Bangkalan Regency. This study used qualitative approached which took place inKelbung Village, Galis District, Bangkalan Regency, Madura. The study used purposive method to obtain informants. The study used a participatory observation techniqueand in-depth interviews to obtain the data. The author analyzed the data using Milles and Huberman interactive technique (reduction, presentation, and conclusion drawing). The philosophy of bhuppha’, bhabhu’, ghuru, ratoh in the context of decision making regarding child marriage inKelbung Village, Galis District, Bangkalan Regency have a meaning that the decision makers regarding child marriage in Kelbung Village are based on these philosophical values.Decision making regarding child marriage in Kelbung Village adheres to the hierarchy within the philosophy of bhuppha’, bhabhu’, ghuru, ratoh where the bhuppha’ figure or the father becomes the first figure who make decisions and his decisions must be obeyed by the daughter to be married. The approach based on the philosophy of bhuppha’, bhabhu’, ghuru, ratoh can be implemented to reduce the number of child marriage by approaching the bhuppha’ figure or the father to provide knowledge and understanding about child marriage.